Avascular Peripheral Retina in Infants - Şengül Özdek; Ece Özdemir Zeydanlı; Caroline Baumal; Sandra Hoyek; Nimesh Patel; Audina Berrocal; Ashley Lopez-Cañizares; Hasenin Al-Khersan; Shunji Kusaka; Fukutaro Mano; Subhadra Jalali; Domenico Lepore; et al. (Türk Oftalmoloji Dergisi, 2023)

(untitled)
Avascular peripheral retina in an infant is a common characteristic of numerous pediatric retinal vascular disorders and often presents a diagnostic challenge to the clinician. In this review, key features of each disease in the differential diagnosis, from retinopathy of prematurity, familial exudative vitreoretinopathy, Coats disease, incontinentia pigmenti, Norrie disease, and persistent fetal vasculature, to other rare hematologic conditions and telomere disorders, will be discussed by expert ophthalmologists in the field.